Design of a novel all-carbon multi-layer structure with excellent thermal protection performance based on carbon/carbon composites and carbon foam. Issue 18 (15th December 2020) - Liu, Xue-Song; Fu, Qian-Gang; Zhang, Jia-Ping; Tong, Ming-De; Ma, Wei-Hao
Abstract: In order to obtain high-performance thermal protection materials, a novel all-carbon triple-layer structure was designed by orderly combining high thermal conductivity carbon/carbon composites (HTC-C/C), polyacrylonitrile-based carbon fiber reinforced composites (PAN-C/C) and carbon foam. During exposure to the oxyacetylene torch, compared with the multi-layer structure made of PAN-C/C and carbon foam, the maximum surface temperature of the triple-layer structure was lowered from 2348 °C to 2215 °C, and the mass ablation rate was reduced by 90.0%, attributed to the excellent heat-dissipation performance and the higher anti-oxidation property of HTC-C/C. When compared with the multi-layer structure composed of HTC-C/C and PAN-C/C, the back surface temperature of the triple-layer structure is further decreased by 700 °C, proving the effective thermal insulation of carbon foam; meanwhile, by isolating the air structure of the intermediate layer made of PAN-C/C was protected from oxidation.